اتجاهات تطور النقل البحري وأهميته في التجارة الخارجية السورية - هرمز, نور الدين; خضرة, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
لعبت التجارة الخارجية دورا هاما في الاقتصاد السوري،لما تمثله من موقع هام في العلاقات الاقتصادية الدولية من خلال دراسة الصادرات والواردات السورية بشكل عام بالاعتماد على موقع سورية الجغرافي الاستراتيجي، ويلعب النقل البحري دوراً مهماً في سورية، فمن خلال تحليل حركة التجارة البحرية،الصادرات والواردات البحرية ونسبتها إلى التجارة الخارجية بالاعتماد على تحليل مؤشرات حركة السفن وتداول البضائع في الموانئ السورية وتطورها،تبين أهمية النقل البحري وخاصة الحاويات حيث وجدنا زيادة واضحة في عدد الحاويات مع توفر نوعية وجودة النقل على اعتبار البنية التحتية المتطورة أحد أهم محددات التنافسية خاصة وأن هناك زيادة طفيفة في كمية البضائع المفرغة والمحملة في الموانئ السورية مع دراسة معدل نمو إيرادات الشركة العامة لمرفأ اللاذقية. 've played foreign trade has an important role in the Syrian economy, because it represents important site in international economic relations through the study of exports and imports Syrian generally relying on Syria's strategic geographic location, and plays a maritime transport has an important role in Syria, it is through the analysis of the movement of maritime trade exports and import smarine and attributed to the foreign trade based on the analysis of indicators of the movement of ships and cargo handling in the Syrian ports and development, showing the importance of maritime transport and special containers and the role they play in the development of maritime transport with the availability of the quality of transport on the grounds advanced infrastructure one of the most important determinants of competitiveness with the study of the growth rate of revenues General Company for the port of Latakia